2011
DOI: 10.4067/s0718-58392011000400009
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and Pre-Lethal Reproductive Effects of Metarhizium anisopliae var. anisopliae on Pseudococcus viburni (Hemiptera: Pseudococcidae)

Abstract: Obscure mealybug, Pseudococcus viburni (Signoret), is a cosmopolitan pest that causes damage by suction of vascular juices and the production of honeydew, as well as for being a quarantine insect. Within control options, entomopathogenic fungi are a good alternative, nevertheless, more research is needed. In this research, the Metarhizium anisopliae var. anisopliae (Metschnikoff) isolate Qu-M984 was evaluated on P. viburni under laboratory conditions. Virulence was evaluated by lethal dose 50 (LD 50 ) and leth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
2
2
0
1
Order By: Relevance
“…Amnuaykanjanasin et al (2013) indicated that strain BCC2660 of B. bassiana (different than the one in our study) required 6 to 7 d to cause complete mortality on the cassava mealybug Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) when sprayed at a 10 8 conidia per mL, greater than what we used herein. Spraying P. viburni females with the same strain of M. anisopliae used in our study, Pereira et al (2011) reported a LC 50 of 3.2 × 10 4 conidia per mL with a mean lethal time (LT 50 ) of 7.4 d on females (closer to our results) but at a lower application rate. Furthermore, Pereira et al (2011) found that the M. anisopliae strain we tested reached a LT 50 on P. viburni in 7.7 to 10.0 d at 7.3 × 10 5 to 4.9 × 10 9 conidia per mL, requiring longer time than our study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Amnuaykanjanasin et al (2013) indicated that strain BCC2660 of B. bassiana (different than the one in our study) required 6 to 7 d to cause complete mortality on the cassava mealybug Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) when sprayed at a 10 8 conidia per mL, greater than what we used herein. Spraying P. viburni females with the same strain of M. anisopliae used in our study, Pereira et al (2011) reported a LC 50 of 3.2 × 10 4 conidia per mL with a mean lethal time (LT 50 ) of 7.4 d on females (closer to our results) but at a lower application rate. Furthermore, Pereira et al (2011) found that the M. anisopliae strain we tested reached a LT 50 on P. viburni in 7.7 to 10.0 d at 7.3 × 10 5 to 4.9 × 10 9 conidia per mL, requiring longer time than our study.…”
Section: Discussionsupporting
confidence: 87%
“…Spraying P. viburni females with the same strain of M. anisopliae used in our study, Pereira et al (2011) reported a LC 50 of 3.2 × 10 4 conidia per mL with a mean lethal time (LT 50 ) of 7.4 d on females (closer to our results) but at a lower application rate. Furthermore, Pereira et al (2011) found that the M. anisopliae strain we tested reached a LT 50 on P. viburni in 7.7 to 10.0 d at 7.3 × 10 5 to 4.9 × 10 9 conidia per mL, requiring longer time than our study. Not surprisingly, we also found that chlorpyrifos was acutely more toxic than the fungal formulations to control female P. viburni.…”
Section: Discussionsupporting
confidence: 87%
“…Few studies have examined changes in egg size in insects in response to pathogens, but an experiment with mealybugs and Metarhizium sp . also found no change (Pereira, Casals, Salazar, & Gerding, 2011). Interestingly, another study with beetles ( Tenebrio molitor ) did find a reduction in egg size when healthy females were mated with fungus‐infected males, which the authors suggest is due to infected males producing reduced resources or the females choosing to invest less (Reyes‐Ramirez et al 2019).…”
Section: Discussionmentioning
confidence: 97%
“…No infection is thus apparent when the conidial dose is lower than the threshold (Devi & Rao 2006). It has been reported that a certain amount of pathogen concentration is required for successful infection, such as 1×10 7 conidia/ml B. bassiana against Metarhizium anisopliae (Metschnikoff) Sorokin (Coleoptera: Meloidae) (Devi & Rao 2006), 1.6×10 8 conidia/m 2 of M. anisopliae (Ascomycota: Hypocreales) against Anopheles gambiae Giles and Culex quinquefasciatus Say (Diptera: Culicidae) (Scholte et al 2003), and 1×10 6 conidia/ml of M. anisopliae isolate Qu-M984 against Pseudococcus viburni (Signoret) (Hemiptera: Pseudococcidae) (Pereira et al 2011). Moreover, higher concentrations of B. bassiana are known to infect Lygus hesperus Knight (Hemiptera: Miridae) even at lower humidity (Dunn & Mechalas 1963).…”
Section: Discussionmentioning
confidence: 99%